Precision anesthesia and pharmacogenomics: a scoping review of personalized drug response - Nikzad, Sarina; Elvir-Lazo, Ofelia Loani; Wong, Robert (Frontiers in Anesthesiology, 2026)
BackgroundAnesthetic agent selection and dosing have historically relied on empirical models without taking into account inter-individual variability in drug response, leading to adverse drug reactions (ADRs). Precision medicine, specifically leveraging pharmacogenomics (PGx), offers a paradigm shift toward personalized anesthesia, enhancing efficacy and safety.MethodsThis scoping review synthesized literature from 2015 to 2025, using systematic database searches and Artificial Intelligence (AI)-powered tools, to identify the most extensively studied genetic variants impacting the pharmacokinetics and pharmacodynamics of common perioperative medications.ResultsKey genetic variants in metabolic enzymes, transporters, and receptors significantly influence anesthetic outcomes. Examples include Reduced Metabolism/Prolonged Effects: Variations in CYP3A4/5 and POR alter midazolam metabolism, risking prolonged sedation. CYP2B6*6 is associated with decreased clearance of propofol and ketamine. BChE deficiency causes significantly prolonged paralysis with succinylcholine. Altered Efficacy/Increased Dose Requirements: OPRM1 118 A > G (G-allele) carriers show a blunted response to morphine, requiring higher doses. CYP2D6 ultra-rapid metabolizers (UMs) can have reduced efficacy of ondansetron and risk toxicity from pro-drugs like codeine and tramadol. Pathogenic mutations in RYR1 and CACNA1S identify patients susceptible to Malignant Hyperthermia from volatile anesthetics. Drug-Drug Interactions (DDIs): PGx overlaps with chronic medications (e.g., antidepressants, beta-blockers) that inhibit CYP2D6, creating a phenoconversion risk that functionally mimics a Poor Metabolizer (PM) phenotype, drastically altering opioid efficacy.ConclusionsPGx holds transformative potential for the field of anesthesiology by offering actionable insights for drug selection and dose adjustment to mitigate ADRs and optimize pain control.